The Relationship Between Old And New Testament: A Study On Contemporary Debate Of Methodology Of The Old Testament Theology - Astika, Made (Sekolah Tinggi Theologia Jaffray, 2013)
From the beginning of the discipline, biblical theologians have differed in theirunderstandings of an accredited basis, task, and method for doing biblical theology.In accordance with the existing problems, the purpose of writing this paper are:In accordance with the existingproblems, the main motive and purposes of writing thisresearch are: First of all, to show the continuity of the relation between the OldTestament and New Testament. Secondly, to explain methodology in doing OldTestament Theology through the investigation of historical and biblicalunderstanding. Finally, to call and challenge every leader and church congregationtogether to analyze methodology of biblical theology in order to develop the propermethodology in doing Old Testament Theology.The conclutions are: The relationship between the Old Covenant and the Newcan be presented as follows: God has only one covenant of grace, and only one eternalpeople - in which a person obtains a share through faith in Christ alone, the CovenantHead and the Adam of the new humanity. Herein lies the unity of Gods eternal plan ofsalvation, and of the Word as His special revelation to man. It must be put in mind thatthe God of the Old Testament is also the God of the New Testament. It should be clearthat the God and Father of the Lord Jesus Christ is the same God who created man andwoman, who established marriage, and who redeemed Israel through the Exodus,foreshadowing the redemption of believers through Christ. The Lord Jesusâ concept ofGod as Father contained a truth not characteristic of the Old Testament, but yet notnegating any Old Testament teaching about God.